METODE MULTISENSORI DALAM LATIHAN BINA BICARA TERHADAP KEMAMPUAN MELAFALKAN KATA PESERTA DIDIK TUNARUNGU TKLB-B - STEVANI DESNASELVA, ELISA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Hearing impairment caused disturbance to the children’s language development. Because of the limitedness of the sound received by the children so they also got limitedness in pronouncing the sound. This research had purpose to know whether there was the influence of multisensory method in speech guide training toward pronouncing words ability to hearing impairment learners in TKLB-B Karya Mulia Surabaya or not. This research applied quantitative approach with pre-experiment kind and one group pre-test – post-test design. The subject observed was class B1 in TKLB-B Karya Mulia Surabaya numbering 7 children. The technique of data collection was in the form of test and the data analysis technique was statistic non parametric with Wilcoxon Match Pairs Test formula. This research indicated that before giving treatment the children’s pronouncing ability had average value 58,75 while after giving treatment it became 83,30. The research indicated that the value of Z counted (Zh) = 2,37 was greater than the critic value of Z table 5% (Zt) = 1,96 (Zh > Zt). Ho was refused Ha was accepted so there was influence of multisensory method in speech guide training toward pronouncing words ability to hearing impairment learners. Keywords: Multisensory, pronouncing words